Edukasi Pembuatan Bakso Campuran Daging Sapi Dengan Ikan Tuna Sebagai Sumber Pangan dan Gizi Serta Pendapatan Masyarakat - Nafly Comilo Tiven (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
This community service aims to provide education and understanding that produces creations and products for the people of Ursana Preparation Village, Inamosol District, West Seram Regency, Maluku Province. The method used in this service is by educating the villagers of Ursana Preparation which is conveyed orally about making meatballs mixed with beef and tuna as a source of food and nutrition as well as income for the village community. The results of the extension activities showed: 1) The response of participants to the extension activities was quite good and enthusiastic, 2) The participants who participated in the extension activities began to implement recommendations, namely making meatballs mixed with beef and tuna as a source of food and nutrition for families and income for village communities.